THE NEGATIVE SIDE OF BRAND ATTACHMENT IN PRODUCING NEGATIVE CONSUMER BEHAVIOR - Cynthia Ayu Manggarani; Lina Regina Notylia; Shine Pintor Siolemba Patiro (Universitas Mercu Buana, 2021)
This research is triggered by the author's concern about a brand that will build a strong bond with consumers regardless of the impact it will have. Previous research conducted in the UK stated that brand attachment not only leads to favorable consumer behavior such as brand loyalty, but also detrimental consumer behavior such as trash-talking, schadenfreude and anti-brand actions which are only moderated by attachment avoidance styles (Japutra et al. , 2018). Trash-talking is different from negative WOM. The purpose of this study was to examine positive behavior (brand loyalty) and negative consumer behavior (trash-talking, schadenfreude, and anti-brand action) due to brand attachment using anxiety attachment style and attachment avoidance style as moderating variables in Indonesia. This study uses an online questionnaire method with a sample of 80 respondents. Furthermore, the data were tested using the PLS-SEM method with the help of the WarpPLS 7.0 software. The results explain that strong brand attachment has a strong influence on brand loyalty, trash-talking, schadenfreude, and anti-brand actions. However, these relationships were not moderated by either anxiety attachment styles or avoidance attachment styles. It can be concluded that the relationship between the brand attachment variable and the brand loyalty variable, the trash-talking variable, the schadenfreude variable and the anti-brand action variable were not moderated by the anxiety attachment style and the avoidance attachment style.